The Role of Educational Technology Based on The Use of Adobe Premiere Pro in Teaching Arabic Remotely Via Videos in The Covid-19 Pandemic: دور تكنولوجيا التعليم على أساس استخدام برنامج أدوب بريمير برو في تعليم اللغة العربية عن بعد عبر الفيديوهات في ضوء جائحة كوفيد 19 - Triadi Wicaksono (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2021)
The role of learning media in teaching and learning is an integral part of the world of Education. Learning Media is everything that can be used to convey messages from teachers to students, to stimulate the thinking power, feelings, and interest of students to learn. In addition, the media can play a role in overcoming the boredom of studying in the classroom. Therefore, teachers must motivate students through various media that are not limited only to the school. COVID-19 is a disease caused by a new coronavirus called SARS-CoV-2. The World Health Organization first became aware of the new virus on December 31, 2019, after reports of a cluster of